ANALISA KELAYAKAN RENCANA PEMBELANJAAN MODAL (CAPEX) PT UNITED TRACTORS TBK (UNTR) DALAM RANGKA MENGANTISIPASI PROYEKSI PERTUMBUHAN BISNIS PERUSAHAAN - Perdana, Adhitya; Arief Budiman (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this study is to determine the performance of PT United Tractors Tbk through cash flow analysis that can be used as a decision-making tool by company and investors. Research approach to be used is quantitative descriptive, data used for analysis is secondary data, which is cash flow reports collected from the website of PT United Tractors Tbk. Data were analyzed using 8 cash flow ratios, namely: ration of operating cash flow, cash flow coverage ratio, interest coverage ratio of the cash, the cash coverage ratio of current liabilities, capital expenditure ratio, the ratio of total debt, the ration of net cash flow and free cash flow adequacy ratio. The results of the analysis indicate that the company's financial performance from 2017 to 2021 ratio generated tends to be deprived, where it seen from 5 ratios are on low average